Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Montoya Cueva, Andrea Alejandra (2019)
This research work identifies whether the current strategies used by the company Camposol in its commercial management are adequate to compete in today's market. For this purpose, a method was followed that consisted of an integral diagnosis (internal and external) of the company, for the identification of its strengths, opportunities and weaknesses and threats (SWOT analysis), and in the mission's revision, vision and current strategies of commercial management. Based on this diagnosis, a proposal was planned for changes in its organizational structure to improve the implementation of strategies. The results of the diagnostic analysis show that: although Camposol is a solid company and has gained good positioning in the market is still expanding and requires structural transformations and categorization in the strategic business units to achieve greater growth in exports especially win the European and Asian market. The suggestions madden were included when redesigning the organization chart of the company where the two business units that the company have should be divided into one of the subcategories of organic products and another of non-organic products; while the second Seafood UEN would be subdivided into fresh and frozen products. Finally, redefine the structure of trading UEN using divisions by continents.